The COVID-19 coronavirus outbreak: October 2020 update - Temte, Jonathan (Henry Stewart Talks, 2020)
Changes in COVID-19 epidemiology since May 2020, The role of young people in a population as a driver for transmission, Current landscape of viral transmission, The continued need for public health measures